2010
DOI: 10.1038/sj.ebd.6400733
|View full text |Cite
|
Sign up to set email alerts
|

Surgical endodontic treatment under magnification has high success rates

Abstract: The advancement in surgical endodontics (eg, the use of the dental operative microscope, no or minimal bevel of the root-end resection, and ultrasonic retrograde canal preparation to a depth of 3-4 mm) has resulted in more precise and predictable surgical procedures, which could not normally be achieved using the traditional surgical endodontic treatment (by means of root-end resection with a 45-degree bevel, retrograde preparation of the canal with bur, and root-end filling under no magnification and inadequa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Although it is presently unknown if and how the type of magnification may affect endodontic treatment outcome (Del Fabbro & Taschieri 2010), it is known that the use of magnification increases the accuracy of the operative procedures and improves diagnostic capability, due to a better visualization of the treatment field. For example, it allows detection of isthmuses, accessory canals or microfractures of the root, which are otherwise difficult to recognize and treat in the absence of proper magnification (de Carvalho & Zuolo 2000, Schwarze et al 2002, von Arx et al 2003, Slaton et al 2003, von Arx 2005, Azarpazhooh 2010. In the present study sample, magnification was reported to be widely used (50% of the respondents using magnification on a regular basis and 21% always).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Although it is presently unknown if and how the type of magnification may affect endodontic treatment outcome (Del Fabbro & Taschieri 2010), it is known that the use of magnification increases the accuracy of the operative procedures and improves diagnostic capability, due to a better visualization of the treatment field. For example, it allows detection of isthmuses, accessory canals or microfractures of the root, which are otherwise difficult to recognize and treat in the absence of proper magnification (de Carvalho & Zuolo 2000, Schwarze et al 2002, von Arx et al 2003, Slaton et al 2003, von Arx 2005, Azarpazhooh 2010. In the present study sample, magnification was reported to be widely used (50% of the respondents using magnification on a regular basis and 21% always).…”
Section: Discussionmentioning
confidence: 62%
“…, Slaton et al . , von Arx , Azarpazhooh ). In the present study sample, magnification was reported to be widely used (50% of the respondents using magnification on a regular basis and 21% always).…”
Section: Discussionmentioning
confidence: 99%